Respuesta :

Answer:

The solution to the system of equations be:

[tex]x=3,\:y=-2[/tex]

Step-by-step explanation:

Given the system of equations

4x-2y = 16

y = -5x+13

Solving the system of equations using the substitution method

[tex]\begin{bmatrix}4x-2y=16\\ y=-5x+13\end{bmatrix}[/tex]

Substitute y = -5x+13 in 4x-2y = 16

[tex]4x-2\left(-5x+13\right)=16[/tex]

[tex]4x+10x-26 = 16[/tex]

[tex]14x-26 = 16[/tex]

Now isolate x for [tex]14x-26 = 16[/tex]

[tex]14x-26=16[/tex]

Add 26 to both sides

[tex]14x-26+26=16+26[/tex]

Simplify

[tex]14x=42[/tex]

Divide both sides by 14

[tex]\frac{14x}{14}=\frac{42}{14}[/tex]

Simplify

[tex]x=3[/tex]

For y = -5x+13

Substitute x = 3

[tex]y=-5\cdot \:3+13[/tex]

Simplify

[tex]y=-2[/tex]

Therefore, the solution to the system of equations be:

[tex]x=3,\:y=-2[/tex]